Blockchain-enabled relay-aided wireless networks for sustainable e-agriculture. (25th January 2021) - Song, Kang; Li, Chunguo
Abstract: In this paper, a blockchain-enabled relay-aided wireless network for sustainable e-agriculture is investigated, where best relay selection scheme based on the maximization of equivalent signal to noise ratio/signal to interference ratio (SNR/SIR) is considered. The performance of best relay selection under α − μ channel are derived in the paper, where closed-form expressions for transmission successful rate (TSR) and overall communication throughput (OCT) with and without interference are obtained. From derivation results, as the number of potential relay nodes increase, TSR and OCT performance will be ameliorated correspondingly. Numerical simulations have been performed to validate the correctness of our derivations.